Keberpihakan Pada Sebuah Produk: Meninjau Faktor Promosi, Citra Merek dan Kualitas Produk Pada Keputusan Pembelian Konsumen - Dessy Marhandrie; Linda Lidyawati; Maurits Sipahutar; Raston Sitio; Parel Naibaho (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to explore the factors that influence consumer bias toward a product when making purchasing decisions. The researcher evaluates the effects of promotion, brand image development, and product quality, focusing on Pepsodent’s marketing efforts across various media platforms. Conducted between March and July 2024 in East Jakarta, the study employs a quantitative approach. Given the unknown population size, the Lameshow formula with a 7% alpha was used to calculate the sample size, resulting in 196 respondents. The research applies a descriptive correlation method to assess the influence of the independent variables (promotion, brand image, and product quality) on the dependent variable (consumer purchasing decisions). Primary data were gathered through questionnaires distributed to respondents, while secondary data were derived from relevant literature and prior studies. Data were processed using SPSS software, employing multiple linear regression analysis. Before conducting regression, the data underwent validity, reliability, and classical assumption tests, including normality, heteroscedasticity, and multicollinearity checks. Findings reveal that, individually, the promotion factor has the highest impact, contributing 72.3% to consumer purchasing decisions. Brand image follows with an influence of 61.4%, while product quality contributes 61.5%. Together, these three independent variables significantly affect consumer purchasing decisions for Pepsodent toothpaste, as demonstrated by the F-Test result of 32.423 at a significance level of 0.00 (p < 0.05). These results highlight the critical role of promotional activities, a strong brand image, and high product quality in shaping consumer preferences and driving purchasing decisions in the competitive toothpaste market in East Jakarta.